International Journal of Technology and Design Education - de Vries, Marc J.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
The International Journal of Technology and Design Education seeks to encourage research and scholarly writing about any aspect of technology and design education. Critical, review, and comparative studies are particularly prominent, as are contributions which draw upon other literatures, such as those derived from historical, philosophical, sociological or psychological studies of technology or design, in order to address issues of concern to technology and design education. One of the most significant developments of recent years has been the emergence of technology and design education as an integral part of general education in many parts of the world. Its distinctive curriculum features are technological literacy and capability and it highlights the importance of `knowledge in action', of `doing' as well as `understanding'. However, teaching technology and design as a component of general education is an emergent, rather than an established, practice and many questions remain to be answered. In addition to issues about the nature of technology itself, little is known about students' learning and teachers' understandings of technology and about what it means to become more technologically capable. There are important issues about the preparation of technology teachers, the assessment of technological competence and the relationship of technology to other curriculum elements, notably science. There are also significant policy questions relating to the practice and rationale of curriculum change.
Keywords: Educational technology; Learning; Instruction; Science education; Educational Technology; Learning and Instruction; Science Education